ISOLASI KUMARIN DARI KULIT BUAH LIMAU SUNDAI (Citrus nobilis Lour) - Melindra Mulia (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
Coumarin has been isolated and characteritated from rind of Citrus nobilis Lour by maseration methode with methanol. After fractionation by n-hexane and ethyl acetate, collected the phase ethyl acetate which positive of coumarin. From ethyl acetate extract coumarin have been isolated by column chromatography. The isolation results was obtain 2,159 g of pure white needle-shape crystalline with the melting point of 126,2-127,60C. Structure of the isolated coumarine was elucidated by spectroscopic methodes, UV-Vis,13C-NMR, 1H-NMR, 2D-NMR (DEPT/HSQC, COSY, NOESY, HMBC) and IR spectra. Based on the spectra data the isolated coumarine is marmin.